Faktor-Faktor yang Mempengaruhi Penerimaan Retribusi Pelayanan Pasar di Kabupaten Solok - Yeni Sofida; Zefriyenni Zefriyenni; Lusiana Lusiana (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to find out the factors that affect the receipt of market service levy in Solok Regency. The type of research used is quantitative. The data analysis techniques used were multiple linear regression analysis and path analysis, by distributing questionnaires as many as 89 samples. The results of the study Market service fee rates have a positive and insignificant effect on the receipt of market service fees in Solok Regency. Human resources have a positive and significant effect on the receipt of market service fees in Solok Regency. Facilities and infrastructure have a positive and significant effect on the receipt of market service fees in Solok Regency. Awareness of mandatory fees has a positive and significant effect on the receipt of market service fees in Solok Regency. Market service fee rates, human resources, facilities and infrastructure and awareness of mandatory fees together have a positive and significant effect on the receipt of market service fees in Solok Regency. The contribution of market service fee rates, human resources, facilities and infrastructure and awareness of mandatory fees to the receipt of market service fees is 0.716 or 71.6%.